Hepar-on-a-sensor-platform with hybridization chain reaction amplification strategy to intuitively monitor the hepatoxicity of natural compounds. (1st April 2023) - Qian, Wenhui; Gong, Guangming; Su, Hua; Zhao, Yang; Fu, Wenjuan; Wang, Yuting; Ji, Wenwen; Sun, Xuetong; Zhang, Bei; Ma, Lijuan; Li, Jianting; Zhang, Xiangying; et al.
Abstract: The irrational use of natural compounds in the treatment of diseases can lead to serious side effects, especially hepatoxicity, and its toxic effects are usually cumulative and imperceptible. Therefore, an accurate sensing platform is urgently needed to monitor the hepatotoxicity of natural compounds. Here, we deposited a thermo-responsive alginate-RGD/Pluronic hydrogel to construct an in vitro three-dimensional(3D) hepar-platform, and a thorough validation was adopted to evaluate the bioprinted hepatic constructs. The engineered hepar-platform was then employed to access its biological response toward Emodin (EM) and Triptolide (TP), two typical hepatotoxic natural compounds. Subsequently, we integrated it with a robust fluorescent sensor based on hybridization chain reaction amplification strategy (HCR) to monitor the early hepatotoxic biomarker - glutathione-S-transferase-alpha (GST-α) secreted by this 3D constructs. Our study was the first attempt to construct an accurate hepar-on-a-sensor platform that could effectively detect GST-α for monitoring the hepatoxic effects of natural compounds. The limit of detection of the platform was 0.3 ng ml −1 and the accuracy of this platform was verified by enzyme linked immunosorbent assay. Furthermore, the variation of GST-α induced by EM and TP was consistent with hepatotoxicity studies, thus providing an important application value for evaluating the hepatotoxicity of natural compounds. Statement of significance: 1. We deposited a thermo-responsive alginate-RGD/Pluronic hydrogel to construct an in vitro three-dimensional(3D) hepar-platform, and elucidated the essential reasons why hybrid bioinks more suitable for 3D extrusion from biomaterials itself. Also, a thorough validation associated with a series of important proteins and genes involved in liver cell metabolism was adopted to evaluate the bioprinted hepatic constructs accurately 2. Glutathione-S-transferase-alpha is a soluble trace biomarker for acute hepatotoxic injury, the hepatotoxic effects of natural compounds on the secretion of GST-α has not been reported to date. We integrated our 3D hepar-platform with recognition molecules-aptamers and HCR amplification strategy to monitor the variation of GST-α, aiming at developing a robust and stable fluorescent biosensing platform to monitor the hepatoxicity of natural compounds Graphical abstract: Image, graphical abstract